Determinants of Sustainability Reporting in the Romanian Banking Sector - Mihaela CUREA; Maria Carmen HUIAN; Marilena MIRONIUC (Audit Financiar)
This paper investigates the determinants of Sustainable Development Goals (SDG) reporting in the Romanian banking sector over an extended time horizon (2017-2023), employing a mixed-method approach that combines content analysis, fixed-effects regression, and regression trees. The analysis covers 17 commercial banks. The results indicate that report size and type are the primary determinants of SDG reporting. Additionally, the study highlights a positive effect of gender diversity on the transparency and quality of reported information, although its influence varies depending on bank-specific characteristics. Other governance factors, such as the frequency of board meetings or the independence of board members, exhibit either a negative or insignificant impact, potentially signaling organizational challenges. While macroeconomic factors such as inflation and economic growth do not have a direct effect on SDG scores, they may amplify the impact of governance variables and bank characteristics. The key contribution of this study lies in integrating two complementary methodological approaches, capturing both overarching relationships and conditional effects. Regression trees facilitate the identification and modeling of non-linear and conditional relationships between variables, enabling the detection of complex interactions that traditional fixed-effects regression models cannot capture. The findings provide a nuanced perspective on the role of board activity and composition in fostering transparency and sustainability in the banking sector.